Conductance switching in an organic material: from bulk to monolayer - Rath, Arup Kumar; Pal, Amlan J. (Langmuir, 2007)
Fluorescein sodium, which does not exhibit electrical bistability in thin films, can be switched to a high conducting state by the introduction of carbon nanotubes as channels for carrier transport. Thin films based on fluorescein sodium/carbon nanotubes display memory switching phenomenon among a low conducting state and several high conducting states. Read-only and random-access memory applications between the states resulted in multilevel memory in these systems. Results in thin films and in a monolayer (deposited via layer-by-layer assembly) show that instead of different molecular conformers, multilevel conducting states arise from the different density of high conducting fluorescein molecules.

CdSe quantum dot-based nanocomposites for ultralow-power memristors - Bera, Jayanta; Betal, Atanu; Sharma, Ashish; Shankar, Uday; Rath, Arup Kumar; Sahu, Satyajit (ACS Applied Nano Materials, 2022)
The explosion in digital communication with the huge amount of data and the internet of things (IoT) led to the increasing demand for data storage technology with faster operation speed, high-density stacking, nonvolatility, and low power consumption for saving energy. Metal chalcogenide-based quantum dots (QDs) show excellent nonvolatile resistive memory behavior owing to their tunable electronic states and control in trap states by passivating the surface with different ligands. Here, we synthesized high-quality colloidal monodispersed CdSe QDs by the hot injection method. The CdSe QDs were blended with an organic polymer, poly(4-vinylpyridine) (PVP), to fabricate an Al\textbackslashCdSe-PVP\textbackslashAl device. Our device shows excellent bipolar nonvolatile resistive random access memory (RRAM) switching behavior with a high current ON/OFF ratio (I-ON/OFF) of 6.1 x 10(4), and it consumes ultralow power. The charge trapping and detrapping in the potential well formed by the CdSe QD and PVP combination result in resistive switching. This CdSe-PVP-based resistive random access memory (RRAM) device with a high I-ON/OFF, ultrafast switching speed, high endurance, low operating voltage, and long retention period can be used as a high-performance and ultralow-power memristive device.
Keywords: memory switching; memristor; metal chalcogenides; nonvolatile; quantum dots

Colloidal MoS2 quantum dots for high-performance low power resistive memory devices with excellent temperature stability - Bera, Jayanta; Betal, Atanu; Sharma, Ashish; Rath, Arup Kumar; Sahu, Satyajit (Applied Physics Letters, 2022)
Conventional memory technologies are facing enormous problems with downscaling, and are hence unable to fulfill the requirement of big data storage generated by a huge explosion of digital information. A resistive random access memory device (RRAM) is one of the most emerging technologies for next-generation computing data storage owing to its high-density stacking, ultrafast switching speed, high non-volatility, multilevel data storage, low power consumption, and simple device structure. In this work, colloidal MoS2 quantum dots (QDs) embedded in an insulating matrix of poly-(4vinylpyridine) (PVP) were used as an active layer to fabricate a RRAM device. The MoS2 QDs-PVP based RRAM device reveals an excellent nonvolatile resistive switching (RS) behavior with a maximum current on-off ratio (I-ON/I-OFF) of 10(5). High endurance, long retention time, and successive ``write-read-erase-read'' cycles indicate high-performance RRAM characteristics. The ultimate power consumption by this RRAM device is considerably low for energy saving. In addition, the MoS2 QDs-PVP based device shows RS behavior even at 130 degrees C. High I-ON/I-OFF, low operating power, high endurance, long retention time, and excellent stability with temperatures reveal that the MoS2 QDs-PVP based device can be a promising candidate for high-performance low power RRAM devices that can be operated at relatively higher temperatures. Published under an exclusive license by AIP Publishing.